Implementasi Model Discovery dengan Metode Make a Match untuk Meningkatkan Motivasi Belajar - Azizah Nur F.N, Delilia; Hadiatur Rahman, Muhammad (IAIN Madura, 2025)
The learning method is an essential component of the learning process. An engaging and interactive learning experience is crucial as it can enhance students' motivation. Monotonous and less varied teaching methods often become an issue, leading to boredom and a lack of enthusiasm among students. Therefore, this study aims to implement the discovery model with the Make a Match method and determine whether this method can improve the learning motivation of Class VIII A students at SMP Negeri 1 Pamekasan. This research employs classroom action research (CAR) conducted in two cycles. The subjects of this study were 31 students from Class VIII A at SMP Negeri 1 Pamekasan. Data collection techniques included observation, interviews, questionnaires, and documentation, while data analysis was performed using observations, questionnaire results, and triangulation techniques. The results show an increase in students' learning motivation, as observed from the first and second cycles. In Cycle I, the average percentage of learning motivation reached 57.25% (Moderate category), and in Cycle II, it increased to 67.48% (High category). This indicates that the discovery model with the Make a Match method can enhance students' learning motivation.